2011
DOI: 10.1590/s0102-09352011000200020
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo e digestibilidade de nutrientes em vacas submetidas a diferentes níveis de concentrado

Abstract: RESUMOAvaliou-se a influência do teor de concentrado na dieta sobre o comportamento ingestivo, o consumo e a digestibilidade aparente de nutrientes em bovinos. Foram utilizadas quatro vacas mestiças, com média de peso de 442,15kg, distribuídas em quadrado latino 4x4, durante quatro períodos de 14 dias, sendo 11 de adaptação e três para coleta de amostras, elaboradas por animal e por período. O comportamento foi avaliado pela observação dos animais a cada 15 minutos por 24 horas, determinando-se tempo de alimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
3
0
8
Order By: Relevance
“…This decrease in digestibility may be related to the greater growth of amylolytic microorganisms and competition with cellulolytic microorganisms (MERTENS, 1994). In the present study, the observed NDF digestibility was above the average 63.80% reported by Goularte et al (2011), who increased the concentrate content (30, 40, 50, and 60%) in the diet of non-lactating dairy cows in the feedlot receiving corn silage, and 49.31% cited by Bürger et al (2000), who increased the dietary concentrate content (30,45,60,75, and 90%) of feedlot Holstein calves fed coast-cross grass hay. Despite this discrepancy in NDF digestibility values observed in the present study and some described in the literature, and considering the very high values obtained here, it should be stressed that the Tanzania grass used had an elevated nutritional value (Table 2), and its supply allowed great selectivity by the animals, unlike studies cited previously.…”
Section: Resultssupporting
confidence: 41%
“…This decrease in digestibility may be related to the greater growth of amylolytic microorganisms and competition with cellulolytic microorganisms (MERTENS, 1994). In the present study, the observed NDF digestibility was above the average 63.80% reported by Goularte et al (2011), who increased the concentrate content (30, 40, 50, and 60%) in the diet of non-lactating dairy cows in the feedlot receiving corn silage, and 49.31% cited by Bürger et al (2000), who increased the dietary concentrate content (30,45,60,75, and 90%) of feedlot Holstein calves fed coast-cross grass hay. Despite this discrepancy in NDF digestibility values observed in the present study and some described in the literature, and considering the very high values obtained here, it should be stressed that the Tanzania grass used had an elevated nutritional value (Table 2), and its supply allowed great selectivity by the animals, unlike studies cited previously.…”
Section: Resultssupporting
confidence: 41%
“…The eating and feeding time included biting, chewing and swallowing of the bolus. Idling consisted of the time spent not feeding, ócio representou o tempo de não apreensão e ingestão e o de não ruminação (GOULARTE et al, 2011).…”
Section: Methodsunclassified
“…According to Goulart et al (2011), an increase in the proportion of concentrate in the diet resulted in a linear decrease of ingestion and rumination in dairy cows. The increase in the proportion of concentrate in the diet reduced the physical effective fiber concentration, thus causing a reduction in rumination time (WELCH;HOOPER, 1988;PEREIRA et al, 2007b;SANTANA JÚNIOR et al, 2013).…”
Section: Resultsmentioning
confidence: 99%